Do Fixed or Mobile Bearing Implants Have Better Survivorship in Medial Unicompartmental Knee Arthroplasty? A Study From the Australian Orthopaedic Association National Joint Replacement Registry. Issue 7 (16th March 2021) - Kannan, Arun; Lewis, Peter L.; Dyer, Chelsea; Jiranek, William A.; McMahon, Stephen
Abstract: Background: During the last 5 years, there has been an increase in the use of unicompartmental knee arthroplasty (UKA) to treat knee osteoarthritis in Australia, and these account for almost 6% of annual knee replacement procedures. However, there is debate as to whether a fixed bearing or a mobile bearing design is best for decreasing revision for loosening and disease progression as well as improving survivorship. Small sample sizes and possible confounding in the studies on the topic may have masked differences between fixed and mobile bearing designs. Questions/purposes: Using data from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR), we selected the four contemporary designs of medial compartment UKA: mobile bearing, fixed modular, all-polyethylene, and fixed molded metal-backed used for the treatment of osteoarthritis to ask: (1) How do the different designs of unicompartmental knees compare with survivorship as measured by cumulative percentage revision (CPR)? (2) Is there a difference in the revision rate between designs as a function of patient sex or age? (3) Do the reasons for revision differ, and what types of revision procedures are performed when these UKA are revised? Methods: The AOANJRR longitudinally maintains data on all primary and revision joint arthroplasties, with nearly 100% capture. The study population included all UKA procedures undertaken for osteoarthritis between September 1999 and December 2018. Of 56, 628 unicompartmental knees recorded during the study period, 50, 380 medial UKA procedures undertaken for osteoarthritis were included in the analysis after exclusion of procedures with unknown bearing types (31 of 56, 628), lateral or patellofemoral compartment UKA procedures (5657 of 56, 628), and those performed for a primary diagnosis other than osteoarthritis (560 of 56, 628). There were 50, 380 UKA procedures available for analysis. The study group consisted of 40% (20, 208 of 50, 380) mobile bearing UKA, 35% (17, 822 of 50, 380) fixed modular UKA, 23% (11, 461 of 50, 380) all-polyethylene UKA, and 2% (889 of 50, 380) fixed molded metal-backed UKA. There were similar sex proportions and age distributions for each bearing group. The overall mean age of patients was 65 ± 9.4 years, and 55% (27, 496 of 50, 380) of patients were males. The outcome measure was the CPR, which was defined using Kaplan-Meier estimates of survivorship to describe the time to the first revision. Hazard ratios from Cox proportional hazards models, adjusted for sex and age, were performed to compare the revision rates among groups. The cohort was stratified into age groups of younger than 65 years and 65 years and older to compare revision rates as a function of age. Differences among bearing groups for the major causes and modes of revision were assessed using hazard ratios. Results: At 15 years, fixed modular UKA had a CPR of 16% (95% CI 15% to 17%). In comparison, the CPR was 23% (95% CI 22% to 24%) for mobile bearing UKA, 26% (95% CI 24% to 27%) for all-polyethylene UKA, and 20% (95% CI 16% to 24%) for fixed molded metal-backed UKA. The lower revision rate for fixed modular UKA was seen through the entire period compared with mobile bearing UKA (hazard ratio 1.5 [95% CI 1.4 to 1.6]; p < 0.001) and fixed molded metal-backed UKA (HR 1.3 [95% CI 1.1 to 1.6]; p = 0.003), but it varied with time compared with all-polyethylene UKA. The findings were consistent when stratified by sex or age. Although all-polyethylene UKA had the highest revision rate overall and for patients younger than 65 years, for patients aged 65 years and older, there was no difference between all-polyethylene and mobile bearing UKA. When compared with fixed modular UKA, a higher revision risk for loosening was shown in both mobile bearing UKA (HR 1.7 [95% CI 1.5 to 1.9]; p < 0.001) and all-polyethylene UKA (HR 2.4 [95% CI 2.1 to 2.7]; p < 0.001). The revision risk for disease progression was higher for all-polyethylene UKA at all time points (HR 1.4 [95% CI 1.3 to 1.6]; p < 0.001) and for mobile bearing UKA after 8 years when each were compared with fixed modular UKA (8 to 12 years: HR 1.4 [95% CI 1.2 to 1.7]; p < 0.001; 12 or more years: HR 1.9 [95% CI 1.5 to 2.3]; p < 0.001). The risk of revision to TKA was higher for mobile bearing UKA compared with fixed modular UKA (HR 1.4 [95% CI 1.3 to 1.5]; p < 0.001). Conclusion: If UKA is to be considered for the treatment of isolated medial compartment osteoarthritis, the fixed modular UKA bearing has the best survivorship of the current UKA designs. Level of Evidence: Level III, therapeutic study.